PENINGKATAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL JIGSAW BERBANTUAN MEDIA BUKU SAKU DI SMP NEGERI 3 WAINGAPU - Mandjarama, Febriany Imerin; Ina, Anita Tamu; Matulessy, Yoin Meissy (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
Jigsaw is a learning model that emphasizes learning on students, namely involving students in groups and solving a problem. This study aims to improve cognitive learning outcomes and students' learning interests through the application of the jigsaw type cooperative learning model in science subjects in class VIII D at SMP Negeri 3 Waingapu. The study was divided into three cycles: The first stage was the pre-cycle which was carried out on July 28, 2025, cycle I was carried out on July 29, 2025, and cycle II was carried out on July 31, 2025. The method used in this study was classroom action research that utilized the Kemmis and Mc Taggart research model which consisted of improving 1). Planning, 2). Action, 3). Observation and 4). Reflection. The results of the study showed that the utilization of the application of the jigsaw type cooperative learning model in science subjects showed significant cognitive learning outcomes and learning interest results. The cognitive learning outcomes in the pre-cycle stage reached a percentage of 43.75%, in the first cycle stage reached a percentage of 71.87%, and in the second cycle stage reached a percentage of 90.62%. It can be seen that each cycle saw a significant increase. The results of students' learning interest in the pre-cycle reached a percentage of 53.12%, in the first cycle reached a percentage of 65.62%, and in the second cycle reached a percentage of 90.62%. ABSTRAKJigsaw merupakan model pembelajaran yang menitik beratkan pembelajaran pada peserta didik yakni melibatkan peserta didik didalam kelompok dan memecahkan suatu masalah. Penelitian ini bertujuan untuk meningkatakan hasil belajar kognitif dan minat belajar peserta didik melalui penerapan model pembelajaran kooperatif tipe jigsaw pada mata pelajaran IPA  di kelas VIII D di SMP Negeri 3 Waingapu. Penelitian dibagi menjadi tiga siklus: Tahap pertama yaitu pra siklus yang dilaksanakan pada tanggal 28 Juli 2025, siklus I dilaksanakan pada tanggal 29 Juli 2025, dan siklus II dilaksanakan pada tanggal 31 Juli 2025. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan kelas yang memanfaatkan model penelitian Kemmis dan Mc Taggart yang terdiri dari peningkatan 1). Perencanaan, 2).Tindakan, 3). Observasi dan 4). Refleksi. Hasil penelitian menunjukkan pemanfaatan penerapan model pembelajaran kooperatif tipe jigsaw pada mata pelajaran IPA terlihat hasil belajar kognitif dan hasil minat belajar yang signifikan. Hasil belajar kognitif pada tahap pra siklus mencapai presentase 43,75%, pada tahap siklus I mencapai presentase 71,87%, dan tahap siklus II mencapai presentase  90,62% dapat terlihat setiap siklus terjadi peningkatan yang signifikan. Hasil minat belajar peserta didik pada pra siklus mencapai presentase53,12%, pada siklus I mencapai presentase 65,62%, dan pada siklus II mencapai presesntase 90,62%.